2013
DOI: 10.1186/2050-6511-14-18
|View full text |Cite
|
Sign up to set email alerts
|

Anvirzel™ in combination with cisplatin in breast, colon, lung, prostate, melanoma and pancreatic cancer cell lines

Abstract: BackgroundPlatinum derivatives are used widely for the treatment of many cancers. However, the toxicity that is observed makes imperative the need for new drugs, or new combinations. Anvirzel™ is an extract which has been demonstrated with experimental data that displays anticancer activity. The aim of the present study is to determine whether the combination of Cisplatin and Anvirzel™ has a synergistic effect against different types of cancer.Materials and methodsTo measure the efficacy of treatment with Cisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 25 publications
(25 reference statements)
1
30
0
Order By: Relevance
“…Cisplatin is also used in combination with natural compounds like osthole in lung cancer cell lines (Xu, Zhang et al, 2013), honey bee venom in ovarian cancer cells (Alizadehnohi, Nabiuni, Nazari, Safaeinejad, and Irian, 2012), anvirzel in breast, colon, lung, prostate, melanoma and pancreatic cancer cell lines (Apostolou, Toloudi et al, 2013), bevacizumab in non-small cell lung cancer-mediated malignant pleural effusion (Du, Li et al, 2013), vinblastine and bleomycin in metastatic granulosa cell tumor of the ovary (Colombo, Sessa et al, 1986), methotrexate, bleomycin and cisplatin for advanced squamous cell carcinoma of the male genital tract (Dexeus, Logothetis et al, 1991). …”
Section: Combination Therapy Of Cisplatin With Other Cancer Drugsmentioning
confidence: 99%
“…Cisplatin is also used in combination with natural compounds like osthole in lung cancer cell lines (Xu, Zhang et al, 2013), honey bee venom in ovarian cancer cells (Alizadehnohi, Nabiuni, Nazari, Safaeinejad, and Irian, 2012), anvirzel in breast, colon, lung, prostate, melanoma and pancreatic cancer cell lines (Apostolou, Toloudi et al, 2013), bevacizumab in non-small cell lung cancer-mediated malignant pleural effusion (Du, Li et al, 2013), vinblastine and bleomycin in metastatic granulosa cell tumor of the ovary (Colombo, Sessa et al, 1986), methotrexate, bleomycin and cisplatin for advanced squamous cell carcinoma of the male genital tract (Dexeus, Logothetis et al, 1991). …”
Section: Combination Therapy Of Cisplatin With Other Cancer Drugsmentioning
confidence: 99%
“…Paclitaxel and cisplatin combination has been used to treat breast cancer, ovarian cancer, and melanoma 1315. Other drugs including doxorubicin,16 gemcitabine,17 vitamin D,18 and other natural compounds like osthole, honey bee venom, and anvirzel have been used with positive outcomes in various cancer treatments 5,19,20…”
Section: Introductionmentioning
confidence: 99%
“…An extract from the leaves of N. oleander synergized with DDP in A549 human lung cancer cells (Calderon‐Montano et al, ). Moreover, the combination of DDP with Anvirzel, a N. oleander extract that is mainly composed of OLE, showed synergism in breast, colon, lung, prostate, melanoma, and pancreatic cancer cells (Apostolou et al, ). These findings suggest that the combination of DDP with OLE has the potential to improve the treatment effect of OS.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies also reported that OLE had an antitumor effect against OS (Ma et al, ; Ma et al, ). The extracts from N. oleander have shown synergistic cytotoxicity when administered with DDP (Apostolou et al, ; Calderon‐Montano, Burgos‐Moron, Orta, Mateos, & Lopez‐Lazaro, ), which suggests that OLE may own the potential to potentiate the effect of DDP. Whether OLE sensitizes DDP in OS cells remains unclear.…”
Section: Introductionmentioning
confidence: 99%